DIFFERENTIATED TEACHING APPROACH TO SUPPORT HIGHLY ABLE STUDENTS IN MIXED CLASSROOMS - -, Yuliati (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2012)
Issues about fulfilling needs of highly able students have been discussed since some years ago. Most highly able students along with their outstanding potential are considered as important aspects of a countryÃ¢â¬â¢s bright future. Their innate gifts which are outstanding need to be nurtured appropriately in order to meet success in their future life. Providing positively supporting environment is essential for them (Tomlinson, 1996). It is inevitable that those highly able students spend most of their time at schools. The support or provision for highly able students is generally far from enough since it is usually given by schools in terms of highly able counselors or learning support for highly able students (Waters et al, 2003). Hardly do schools provide highly able students with challenges within the subjects or curriculum enrichment. Meanwhile, possibility to adjust curriculum by using differentiated teaching approach in order to meet their need is possible. In this paper, I analytically describe the reasons or justification of giving special supports to highly able students in general mixed classrooms. Some components on how to adjust curriculum to meet or fulfill highly able studentsÃ¢â¬â¢ needs are also revealed. This differentiated teaching approach, even though mostly intended to support highly able students, is also beneficial for other students in the classrooms.